STABILITY SOLUTION OF DYNAMICAL SYSTEMS ON A PART OF THE VARIABLES (Scientific journal of the Fergana State University, 2023)
The article deals with mathematical models of dynamic systems, represented by nonlinear differential equations of classical mechanics and biophysics, as well as their new modifications and transformations. The properties of equations, properties of solutions, non-stationary equilibrium and equilibrium situations of the solution are studied.